THE DILEMMA BETWEEN ECONOMIC AND SOCIAL OBJECTIVES IN STATE ENTERPRISES: A Study of Surya Sembada Regional Drinking Water Company (PDAM) In Surabaya City - Billiyanto, Rendy; Mardiyanta, Antun; Setijaningrum, Erna (DIA: Jurnal Administrasi Publik, 2021)
<span style="font-size: 12.0pt; line-height: 107%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">The objective of the study was to explain the phenomenon of the dilemma of policy objectives faced by Surya Sembada Regional Drinking Water Company (PDAM) in Surabaya City.<span style="font-size: 12.0pt; line-height: 107%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">State enterprises work with two policy objectives: social and economic objectives. Studies on the dilemma of policy objectives have not been specifically conducted on state enterprises, g<span style="font-size: 12.0pt; line-height: 107%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: Calibri; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">iven that <span style="font-size: 12.0pt; line-height: 107%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">the involvement of political elements cannot be separated from the business processes of state enterprises. This study attempts to exami<span style="font-size: 12.0pt; line-height: 107%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: Calibri; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN">ne<span style="font-size: 12.0pt; line-height: 107%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;"> the theoretical findings of<span style="font-size: 12.0pt; line-height: 107%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: Calibri; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;"> Lipsky’s conflict of policy objectives<span style="font-size: 12.0pt; line-height: 107%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;"> (2010). Furthermore, Groenendyk (2013) and Christensen et al. (2018) also develop academic results on the reprioritization of policy objectives from elected officials. This study using phenomenology research. The analysis in this study is based on in-depth interviews with executives, legislative, bureaucrats, company managers, and observations and literature studies to support the findings. The results found three things. First, each social and economic objective has five aspects. Second, conflicts still exist between these policy objectives even though Surya Sembada Regional Drinking Water Company (PDAM) has succeeded in achieving its social and economic policy objectives. Third, the reprioritization of the policy objectives from the elected officials (mayors and council members) is dominated by<span style="font-size: 12.0pt; line-height: 107%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: Calibri; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;" lang="IN"> the role of<span style="font-size: 12.0pt; line-height: 107%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;"> mayors who strengthen social objectives.